Centralized RSU deployment strategy for effective communication in multi-hop vehicular Adhoc Networks (VANETs - Rashid, Sami Abduljabbar; Audah, Lukman; Hamdi, Mustafa Maad; Abdulsattar, Nejood Faisal; Mutar, Mohammed Hasan; Alkhafaji, Mohamed Ayad (2023)
Due to the advent of smart cities, vehicular technologies are high focus to perform intelligent transmission. Road traffic control and accident control becomes a primary tasks in Vehicular Adhoc Networks (VANETs). In VANETs communication is ineffective without presence of Road Side Units (RSUs). In some places due to lack of RSUs data transmission is improve as well as end to end delay and routing overhead is increased during the time of communication so effective RSU deployment is very essential to provide effective communication in multi-hop VANETs. In this paper, Centralized RSU Deployment Strategy is proposed to control and monitor the traffic density of the vehicle. The parameters which are considered for the process of centralized RSU deployment strategy are centralization scale, past transmission rate and location identification. To analysis the performance of the network the simulation is carried out in NS2.35 and SUMO. The parameters which are taken for the performance analysis are packet delivery ratio, end to end delay, routing overhead and packet loss. In order to execute comparative analysis the recent research works are considered which are AVRCV and RDSTDV. From the outcome it is understood that the proposed CRDSMV approach achieves 70ms to 200ms lower end to end delay, 7% to 14% improved packet delivery ratio, and 50 packets to 300 packets lower routing overhead and 50 Kbps to 240 Kbps improved throughputs when compared with the earlier methods AVRCV and RDSTDV